A versatile drug delivery system targeting senescent cells - Muñoz‐Espín, Daniel; Rovira, Miguel; Galiana, Irene; Giménez, Cristina; Lozano‐Torres, Beatriz; Paez‐Ribes, Marta; Llanos, Susana; Chaib, Selim; Muñoz‐Martín, Maribel; Ucero, Alvaro C; Garaulet, Guillermo; Mulero, Francisca; et al. (EMBO molecular medicine, 2018)
Senescent cells accumulate in multiple aging‐associated diseases, and eliminating these cells has recently emerged as a promising therapeutic approach. Here, we take advantage of the high lysosomal β‐galactosidase activity of senescent cells to design a drug delivery system based on the encapsulation of drugs with galacto‐oligosaccharides. We show that gal‐encapsulated fluorophores are preferentially released within senescent cells in mice. In a model of chemotherapy‐induced senescence, gal‐encapsulated cytotoxic drugs target senescent tumor cells and improve tumor xenograft regression in combination with palbociclib. Moreover, in a model of pulmonary fibrosis in mice, gal‐encapsulated cytotoxics target senescent cells, reducing collagen deposition and restoring pulmonary function. Finally, gal‐encapsulation reduces the toxic side effects of the cytotoxic drugs. Drug delivery into senescent cells opens new diagnostic and therapeutic applications for senescence‐associated disorders. Synopsis Senescent cells are present in many diseases where they play an active pathological role. A common feature of senescent cells is their high content of lysosomes. Here, it is reported a pharmacological vehicle with lysosomal tropism that preferentially releases drugs into senescent cells. Drugs encapsulated with galacto‐oligosaccharides (gal‐encapsulation) are released into cells after digestion with lysosomal β‐galactosidase and this happens more efficiently in senescent cells. After intravenous injection, gal‐encapsulated drugs preferentially deliver their cargo into pathological tissues with high content of senescent cells. Gal‐encapsulated doxorubicin ameliorates lung fibrosis in mice, reducing collagen and recovering normal breathing, and this is in contrast to free doxorubicin. When xenograft tumors in mice are treated with chemotherapy, a fraction of tumor cells undergo senescence, and concomitant treatment with gal‐encapsulated doxorubicin results in full tumor regression. Gal‐encapsulation prevents the exposure of non‐pathological tissues to drugs and therefore reduces their associated toxicities, as it is shown for doxorubicin cardiotoxicity and for navitoclax‐induced thrombocytopenia. Graphical Abstract Senescent cells are present in many diseases where they play an active pathological role. A common feature of senescent cells is their high content of lysosomes. Here, it is reported a pharmacological vehicle with lysosomal tropism that preferentially releases drugs into senescent cells.